Gambaran Sense of Belonging Mahasiswa Program Studi Bimbingan dan Konseling Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa - Latifah Latifah; Rizky Andana Pohan; Muhammad Nasir (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2021)
Latifah, 2020, Overview of the Sense of Belonging of Students in the Islamic Guidance and Counseling Study Program, Faculty of Ushuluddin Adab and Da'wah at IAIN Langsa. Based on the researchers' assumption, there is a diversity in the level of the sense of belonging that BKI Study Program students have. This is because there are differences in their reasons for participating in activities that support study programs, maintaining the facilities provided and so on. The objective of this research has to describe the sense of belonging of the students of the Islamic Guidance and Counseling Study Program, the Faculty of Ushuluddin Adab and Da'wah IAIN Langsa. Researcher used a descriptive quantitative research method approach which was carried out to BKI Study Program students as many as 63 people with a measurement scale technique using a scale constructed from belongingsess theory by Roy Baumeister and Mark Leary. The results showed that BKI Study Program students have diversity in the sense of belonging. But overall, the average score obtained is 68.21, it shows that BKI Study Program students have a high level of sense of belonging.